Health Locus of Control in Parents of Children with Leukemia and Associations with Their Life Perceptions and Depression Symptomatology - Marta Tremolada; Livia Taverna; Sabrina Bonichini; Maria Caterina Putti; Marta Pillon; Alessandra Biffi (Children, 2020)
In childhood cancer, parents have an important role in the promotion of their children’s wellbeing and in their adoption of a locus of control style towards their children’s health. The current study aimed at identifying types of locus of control in parents of children with leukemia and the possible association with depressive symptomatology and current life perception. One hundred and four parents were recruited at the Hematology–Oncology Clinic of the Department of Woman’s and Child’s Health, University of Padua, one month after a leukemia diagnosis. Participants were Caucasian with a mean age of 37.28 years (SD = 5.89), mostly mothers (87.5%) and with a mean of 12.16 years of education (SD = 3.82). After signing the informed consent, they filled in the Ladder of Life, the Brief Symptom Inventory-18 and the Parental Health Locus of Control (PHLOC) questionnaires. Paired-samples t-test (t = −14.42; df = 103; p = 0.0001) showed that parents of children with leukemia were more inclined to have an external locus of control than an internal one. The hierarchical regression analysis model (R2 = 0.34; F = 4.32; p = 0.0001) identified health professional influence (ß = −0.28; p = 0.004), current life perception (ß = −0.3; p = 0.013) and future life perception (ß = −0.26; p = 0.012) as significant predictors of parental depression. Current life perception was best predicted (R2 = 0.25; F = 3.96; p = 0.01) by the parental influence locus of control style (ß = 0.25; p = 0.03). Improving trust in the medical staff care and strengthening the internal locus of control in parents could be a preventive program to cope with parental depression symptomatology.